2001
DOI: 10.1046/j.1444-2906.2001.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of characteristics of actomyosin from white, pink, and red muscle fiber types in cultured carp

Abstract: The present study compared and examined the characteristics of actomyosin among white (W), pink (P), and red (R) muscle fiber types in carp (cultured). Both the superprecipitation reaction and the Mg2+‐ATPase activity of actomyosin became higher with increased Ca2+ concentration (pCa 7.0–pCa 5.0) and with decreased adenosine triphosphate (ATP) concentration (3.0–0.5 mM) in all three muscle fiber types. A comparison of the three fiber types shows that the superprecipitation reaction of actomysoin was lower in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…We have also reported that the Ca 2+ sensitivity of actomyosin Mg 2+ ‐ATPase increased with Ca 2+ concentration from pCa 7.0 to 5.0, and the rigor mortis progressed at fastest rates and reached the maximum levels at near pCa 5.0 in the cultured Japanese flounder, as well as in cultured and wild red sea breams . In the cultured carp, however, the pink muscle fiber showed higher Ca 2+ sensitivity of the superprecipitation reaction at pCa 5.0, but lower Ca 2+ sensitivity of actomyosin Mg 2+ ‐ATPase activity compared with white muscle fibers . The slopes of the regression lines between Mg 2+ ‐ATPase activity and superprecipitation reaction, however, were different not only among fish species but also between fish specimens of the same species, resulting in different increasing rates of the superprecipitation reaction with increase in Mg 2+ ‐ATPase activity.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…We have also reported that the Ca 2+ sensitivity of actomyosin Mg 2+ ‐ATPase increased with Ca 2+ concentration from pCa 7.0 to 5.0, and the rigor mortis progressed at fastest rates and reached the maximum levels at near pCa 5.0 in the cultured Japanese flounder, as well as in cultured and wild red sea breams . In the cultured carp, however, the pink muscle fiber showed higher Ca 2+ sensitivity of the superprecipitation reaction at pCa 5.0, but lower Ca 2+ sensitivity of actomyosin Mg 2+ ‐ATPase activity compared with white muscle fibers . The slopes of the regression lines between Mg 2+ ‐ATPase activity and superprecipitation reaction, however, were different not only among fish species but also between fish specimens of the same species, resulting in different increasing rates of the superprecipitation reaction with increase in Mg 2+ ‐ATPase activity.…”
Section: Discussionmentioning
confidence: 70%
“…The incubation and superprecipitation reaction of actomyosin were measured by the same method described in our previous report, which followed the method of Ebashi . The combinations of Ca 2+ and ATP concentrations were (i) pCa 7.0, 6.5, 6.0, 5.0, 4.0 and 3.0 at constant 1.0 mmol L –1 ATP, and (ii) 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 mmol L –1 ATP at constant pCa 5.0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dissolved proteins and water form the continuous phase during paste homogenizing, but the indissoluble myofibrillar protein is dispersed in continuous phase in form of lump. It is known that the proportion of continuous phase to disperse phase is highly related to the gel forming ability [8−10] , water-holding capacity [11] , emulsifying ability [12] and so on. Na + [13−14] , Ca 2+ [15−17] and water can influence the dissolving and cross-linking of proteins, then affect the viscoelasticity of surimi gel.…”
Section: Introductionmentioning
confidence: 99%